Effects of anode spacing and flow rate on energy recovery of flat-panel air-cathode microbial fuel cells using domestic wastewater. (June 2018) - Park, Younghyun; Nguyen, Van Khanh; Park, Seonghwan; Yu, Jaecheul; Lee, Taeho
Highlights: The FA-MFC with shortest anode spacing produced the highest electrical energy. NERV showed a negative correlation with flow rate in all anode spacings. NERCOD was correlated with COD removal rate, independent of anode spacing. The FA-MFC has a great potential to recover energy from low-strength wastewater. Abstract: A flat-panel air-cathode microbial fuel cell (FA-MFC) is known to overcome the low conductivity and biodegradability of domestic wastewater. This study evaluated the normalized energy recovery (NER) based on the volume of wastewater treated (NERV ) and chemical oxygen demand (COD) removal (NERCOD ) using FA-MFCs with three anode spacing conditions and different flow rates (within a hydraulic retention time of 30 min). Generation of current was similar (11.7 ± 0.5 mA) at different spacings; however, COD removal was affected by the flow rates. The NERV for both acetate and domestic wastewater showed good agreements with the flow rates in all anode spacing conditions. The NERCOD results were negatively correlated with the COD removal rates, independent of the anode spacing. The FA-MFCs yielded an NERCOD of 0.22 kWh/kg-COD from extremely low-strength domestic wastewater (150 mg-COD/L). The FA-MFC has a significant potential as an energy-sustainable wastewater treatment technology.